Circularly polarized luminescence from Tb(iii) interacting with chiral polyether macrocycles. Issue 43 (11th October 2022) - Homberg, Alexandre; Navazio, Federica; Le Tellier, Antoine; Zinna, Francesco; Fürstenberg, Alexandre; Besnard, Céline; Di Bari, Lorenzo; Lacour, Jérôme
Abstract : Chiral amide-based bis-pyridine polyether macrocycles interact with lanthanides. In the case of luminescent Tb(iii ), the host-guest interaction can be observed by the ligand-centered ECD and by Tb-centered CPL. Abstract : A straightforward two-step synthesis protocol affords a series of chiral amide-based bis-pyridine substituted polyether macrocycles. One ligand is particularly able to complex terbium(iii ) ions spontaneously. Upon complexation, interesting chiroptical properties are observed both in absorbance (ECD) and in fluorescence (CPL). In ligand-centered electronic circular dichroism, a sign inversion coupled with a signal enhancement is measured; while an easily detectable metal-centered circularly polarized luminescence with a g lum of 0.05 is obtained for the main 5 D4 → 7 F5 terbium transition. The coordination mode and structure of the complex was studied using different analysis methods (NMR analysis, spectrophotometric titration and solid-state elucidation).